The high-resolution FTIR spectrum of the v6 band of C2H3D - Tan, T. L. (Animo Repository, 2010)
The absorption spectrum of the ν6 band of C2H3D centered near 1125.27674cm −1 in the 1100–1250cm −1 region was recorded with an unapodized resolution of 0.0063cm −1 using a Fourier transform infrared (FTIR) spectrometer. A total of 947 infrared transitions of the A–B hybrid-type band were assigned and fitted to upper-state (ν 6 =1) rovibrational constants using a Watson’s A-reduced Hamiltonian in the I r representation up to eighth-order centrifugal distortion terms. The b-type infrared transitions of the band were analyzed for the first time. The root-mean-square deviation of the fit was 0.00062cm −1 . The ground-state rovibrational constants up to eighth-order terms were also obtained by a fit of 617 combination differences from the present infrared measurements, simultaneously with 21 microwave frequencies with a root-mean-square deviation of 0.00055cm −1 . From this work, the upper-state (ν 6 =1) and ground-state constants of C2H3D were derived with the highest accuracy, so far. The a- and b-type transitions of the hybrid ν 6 band were found to be relatively free from local frequency perturbations. The ratio of the a- to b-type vibrational dipole transition moments (μ a /μ b ) was found to be 1.05±0.10. From the ν 6 =1 rovibrational constants obtained, the inertial defect Δ 6 was calculated to be 0.3570±0.0008μÅ 2 .